(untitled) (Castilla. Estudios de Literatura, 2020)
The Argentine magazine La Semana Universal published on March 14, 1912 a story by Emilia Pardo Bazán, “Fatum”, of which until now there was no news and whose subject alluded to the possibility of a new uprising in the Rif, following the landing de Larache, in June 1911. In addition to collecting its text, this note raises why that text did not appear in the Spanish periodic press and its author did not rescue it in any of its collections of short stories